Thermomechanical properties of high martensitic Dual-phase steels related to dislocation structures and void damage evolution. Issue 2 (2nd April 2016) - Hug, Eric; Martinez, Mayerling; Chottin, Jerôme
Abstract: This work provides an experimental analysis of the evolution of the microstructure of a DP1000 alloy submitted to thermomechanical loadings. A strong degradation of the mechanical properties is observed for temperatures higher than 423 K linked to microstructural damage mechanisms quantified by void density measurements. Transmission electron microscopy shows that different microstructure parameters such as ferrite grain size and shape, volume fraction of martensite and carbide precipitation need to be taken into account in order to understand the thermomechanical behaviour of DP1000 steels. A critical void area fraction and a critical equivalent plastic strain were identified from each temperature level and these parameters were considered as a fracture criterion in the Johnson–Cook model. These experimental results could help improving shaping processes of these alloys.